PEMANFAATAN DUA JENIS KOMPOS GANGGANG COKLAT (Sargassum polycystum) DALAM MENINGKATKAN KESUBURAN TANAH ULTISOL SERTA PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Topan Radika Pranata Siregar; Alida Lubis; Supriadi Supriadi (Jurnal Agroekoteknologi, 2014)
This reseach aimed to determines differences ability between two types of the brown algaecompost increase fertility of Ultisol and mustard production. This research was conducted inCompos Centre, Gauze House, Laboratory of Chemistry And Soil Fertility ,Laboratory of Researchand Technology Agriculture Faculty, University of North Sumatera, Medan in March-October2013. The method used non-factorial randomized block design consisting of 11 treatments with 3replications. R0 (control), R1, R2, R3, R4, and R5 with application of 50 g, 100 g, 150 g, 200 g, and250 g brown algae compost respectively, R6, R7, R8, R9, dan R10 with application of 50 g, 100 g,150 g, 200 g, and 250 g brown algae add chicken dirt compost respectively.The results showed thatapplication of two types compost able to increase the pH, C-organic, N-total, K-exchange in thesoil as well as increase the plant height, plant fresh weight, plant dry weight and root dry weight. Atparameters of soil pH, the K-exchange soil, application of brown algae compost significantlydifferent with brown algae added chicke dirt compost. The best dosage of brown algae add chickendirt compost 150 g /polybag for the K-exchange soil and soil pH.Keywords : The brown algae compost, chicken dirt, mustard.